Position Control of Pneumatic Actuator Using Self-Regulation Nonlinear PID - Syed Salim , Syed Najib; Rahmat, Mohd Fua’ad; Mohd Faudzi, Ahmad ’Athif; Ismail, Zool H.; Sunar, Noorhazirah (2014)
he enhancement of nonlinear PID (N-PID) controller for a pneumatic positioning system is proposed to improve the performance of this controller. his is executed by utilizing the characteristic of rate variation of the nonlinear gain that is readily available in NPID controller. he proposed equation, namely, self-regulation nonlinear function (SNF), is used to reprocess the error signal with the purpose of generating the value of the rate variation, continuously. With the addition of this function, a new self-regulation nonlinear PID (SN-PID) controller is proposed. he proposed controller is then implemented to a variably loaded pneumatic actuator. Simulation and experimental tests are conducted with diferent inputs, namely, step, multistep, and random waveforms, to evaluate the performance of the proposed technique. he results obtained have been proven as a novel initiative at examining and identifying the characteristic based on a new proposal controller resulting from N-PID controller. he transient response is improved by a factor of 2.2 times greater than previous N-PID technique. Moreover, the performance of pneumatic positioning system is remarkably good under various loads.